2021
DOI: 10.1590/1414-431x2020e9570
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aspirin, vitamin D3, and progesterone on pregnancy outcomes in an autoimmune recurrent spontaneous abortion model

Abstract: High proportions of placental lymphocytes expressing DX5+/CD25+/FOXP3+/CD45+/CD4+ are beneficial to maintain immune tolerance and improve pregnancy outcomes. This study aimed to compare and evaluate the therapeutic effects of aspirin, vitamin D3 (VitD3), and progesterone on the autoimmune recurrent spontaneous abortion (RSA) model. The autoimmune RSA mouse model was constructed, and the embryo loss rate was calculated for each group. Then, primary mouse placental lymphocytes were isolated, and the expression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
(36 reference statements)
1
2
0
Order By: Relevance
“…Thus, the combination of progesterone and vitamin D3 may have a synergistic effect on stimulating the polarization of macrophages towards the predominance of the M 2 phenotype. Similar results were obtained by Chen Y. et al when studying the effect of the progesterone-vitamin D3 complex on the immunological status and pregnancy outcomes in rats with an autoimmune model of spontaneous abortions [ 38 ].…”
Section: Discussionsupporting
confidence: 85%
“…Thus, the combination of progesterone and vitamin D3 may have a synergistic effect on stimulating the polarization of macrophages towards the predominance of the M 2 phenotype. Similar results were obtained by Chen Y. et al when studying the effect of the progesterone-vitamin D3 complex on the immunological status and pregnancy outcomes in rats with an autoimmune model of spontaneous abortions [ 38 ].…”
Section: Discussionsupporting
confidence: 85%
“…RSM accounts for approximately 2–5% of the total pregnancies [ 2 ]. Although concentrated research has identified numerous causes of RSM, such as chromosomal abnormalities, abnormal reproductive structure, endocrinopathies, and thrombophilic disorders, 50% of RSM cases are still unexplained [ 3 ]. Exploring the pathogenesis of unexplained RSM and providing early intervention are critical for ensuring a better pregnancy outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Further, PRG switches the immune reaction from pro-inflammatory to antiinflammatory, facilitating Treg cell differentiation and the downregulation of IFN-γ generated by natural killer (NK) cells [20]. Based on its neuroprotective and anti-inflammatory functions, PRG is considered a drug candidate for the treatment of various inflammatory and autoimmune diseases [21][22][23][24]. Treatment with PRG can reduce the signs of EAU in mice, decrease IL-17 levels, and increase IL-10 levels [22].…”
Section: Introductionmentioning
confidence: 99%